Policy framework for Myanmar rice production and in-depth study on greenhouse gas emissions - Sander, BO; Lai, Lai (Scientific Research and Community Ltd, 2021)
This study assesses the interactive nature of rice and climate change in the context of Myanmar, one of the largest rice-producing countries. In the first section, special emphasis is given to the current situation of Myanmar’s rice production as affected by climate change alongside with possible adaptation strategies. Since only a small share (23.6 %) of the rice area is irrigated, low precipitation climate extremes directly translate into either drought problems due to limited access of water in case of drought or flood problems due to limited drainage. Moreover, more than half of the national rice production derives from the Ayaryewady delta, so that Myanmar’s food security is very susceptible to impacts triggered tropical cyclones such as “Nargis” in 2008. The scope of adaptation to climate change is elaborated at different levels ranging technical options for increasing resilience of the rice crop to policies that alleviate risks for farmers.